Метод Ньютона для неявной схемы численного интегрирования уравнений газовой динамики - Ершов, С.В.; Деревянко, А.И.; Гризун, М.Н. (Проблемы машиностроения, 2010)
Для нестационарной системы уравнений Эйлера построена неявная итерационная схема. Пространственные производные исходных уравнений аппроксимируются полностью неявно, а производные по времени приближаются односторонней трехточечной разностью. Нелинейная система алгебраических уравнений решается методом Ньютона. Рассмотрены вопросы аппроксимации и устойчивости неявной схемы и предложена ее модификация, уменьшающая численные осцилляции решения. Приведены результаты численного эксперимента. Для нестаціонарної системи рівнянь Ейлера побудована неявна ітераційна схема. Просторові похідні вихідних рівнянь апроксимуються повністю неявно, а похідні за часом наближаються однобічною триточковою різницею. Нелінійна система алгебраїчних рівнянь розв’язується методом Ньютона. Розглянуто питання апроксимації та стійкості неявної схеми та запропоновано її модифікацію, яка зменшує чисельні осциляції розв’язку. Наведено результати чисельного експерименту. The iterative implicit scheme is constructed for unsteady Euler equations. Time derivatives of the governing equations are approximated by one-sided three-point differences, whereas spatial derivatives are approximated fully implicitly with a finite-volume approach, ENOreconstruction and the Gounod’s exact Riemann solver. The nonlinear system of the algebraic equations is solved by the Newton method. The implicit iterative scheme constructed here is devoid of errors of factorisation, linearisation and diagonalisation of implicit operator. Approximation and stability of the scheme are considered. To reduce unphysical numerical oscillations at large Courant numbers we suggest the scheme modification that uses choice of smooth stencil for time derivatives. The results of numerical experiment are presented.